Experimental infection of broiler chickens with Campylobacter jejuni - Joaquim, Patricia Estefania; Balbiani, Facundo; Socas, Maria Laura; Chacana, Pablo (Asociación Española de Ciencia Avícola, 2026)
Poster de la Presentación